Membrane-bound phosphatases in Escherichia coli: sequence of the pgpB gene and dual subcellular localization of the pgpB product. - Icho, T (1988)
The phosphatidyl glycerophosphate B phosphatase of Escherichia coli has a multiple substrate specificity and a peculiar dual subcellular localization in the envelope. Its phosphatidyl glycerophosphate phosphatase activity is higher in the cytoplasmic membrane, while phosphatidic acid and lysophosphatidic acid phosphatase activities are higher in the outer membrane. The DNA sequencing of the pgpB gene revealed a protein of 251 amino acids which had at least five hydrophobic membrane-spanning regions. About 37 hydrophilic residues in the middle of the sequence had considerable homology with the C-terminal conserved region of the ras family genes in eucaryotes. A protein of 28,000 daltons was expressed from the pgpB gene under a tac promoter in a runaway replication plasmid. This overproduced protein also revealed the dual subcellular localization.